Mexico and the tobacco industry: doing the wrong thing for the right reason?. Issue 7537 (9th February 2006) - Samet, Jonathan; Wipfli, Heather; Perez-Padilla, Rogelio; Yach, Derek
Abstract : By linking payments to a health fund with sales of cigarettes, the tobacco industry is undermining international agreements to control smoking